Substantiation of Rational Values of the Basic Parameters of a Bulldozer Blade for Leveling Municipal Solid Waste - Khankelov, Tavbay Karshiyevich; Aslonov, Norkul Rabbonayevich; Kudaybergenov, Mavlyan Saidakbarovich; Djumabaeva, Fotima Irkinovna; Saidova, Shoira Shagiyazovna (International Journal of Psychosocial Rehabilitation, 2020)
Solid waste management is an acute and widespread problem in both urban and rural areas of many developed and developing countries. The collection and disposal, as well as the disposal of municipal solid waste (MSW), is today one of the main environmental problems. Any solution for processing solid waste should be financially sustainable, technically feasible, socially and legally acceptable, as well as environmentally friendly.This article is devoted to an urgent problem, the development of a criterion dependence of the leveling process of a solid bulldozer blade with a solid waste dump, which in turn will serve as a link between a theoretical analysis and an experimental study of this process. Based on the established analytical dependencies and restrictions arising from the properties of the waste, as well as on the basis of the accuracy of the measuring instruments, a linear scale is determined. The experimental studies carried out on physical models allowed a simple multiplication of the linear scale by the values of the parameters obtained experimentally from the blade, and rational values of the main parameters of a real bulldozer will be obtained.